University curriculum reform and employability: addressing the needs of the post-colonial workforce - Dyantyi, Ntsika (Frontiers in Education, 2025)
The South African higher education landscape continues to grapple with persistent challenges despite significant policy reforms introduced by the democratic government. Epistemologies and knowledge systems in most universities remain deeply rooted in Western worldviews, limiting the inclusivity and relevance of curricula in addressing the socio-economic needs of a post-colonial workforce. This study employed an interpretive qualitative approach, utilizing narrative analysis to examine data collected from semi-structured interviews with 3 lecturers and 1 curriculum transformation manager at a university in the Eastern Cape region of South Africa. Key findings include the infusion of entrepreneurship education and digital literacy to bridge the skills gap and ensure graduates possess competencies that align with contemporary workforce needs. Incorporating various cultural identities, ideologies, and languages into curricula can create an inclusive learning environment that fosters critical thinking and social justice. This paper recommended that challenging Eurocentric perspectives, promoting multilingualism, and leveraging technology responsibly will decolonise university curricula and prepare graduates for meaningful participation in a dynamic and globalized economy.